The Relationship between the Korean Dawn Prayer Meeting and Spirituality. (September 2019) - Kim, Jonghyun
This article analyzes the formative power of the Korean dawn prayer service to better understand the public and private dimensions of Christian spirituality. It explores the origin of the dawn prayer in the history of Korean Protestantism, and examines an example from a particular church. On the basis of this exploration, it is argued that the dawn prayer service should not be understood as an instrument to strengthen individual spirituality, but rather as a place to participate in God's redemptive work to and for the world. Both the individual and communal aspects of dawn prayer practice are important, but I will argue that current Korean practice leans too much toward the individual.